Palladium-catalysed synthesis of triaryl(heteroaryl)methanes - Shuguang Zhang; Byeong-Seon Kim; Chen Wu; Jianyou Mao; Patrick J. Walsh (Nature Communications, 2017)
Molecules with 4 aryl groups attached to a central carbon atom have proven challenging to synthesize despite their attractiveness for a variety of applications. Here the authors report a Pd-catalysed arylation of di- and triarylmethanes, giving a high-yielding route to an array of tetraarylmethanes.